A dog's perfect Christmas - Cameron, W. Bruce (Forge, 2020)
The problems fracturing the Goss family as Christmas approaches are hardly unique, though perhaps they are handling them a little differently than most people might. But then a true emergency arises, one with the potential to not only ruin Christmas, but everything holding the family together. Is the arrival of a lost puppy yet another in the string of calamities facing them, or could the little canine be just what they all need?